Encyclopedia of Hydrological Sciences 2005
DOI: 10.1002/0470848944.hsa122
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Land Cover Effects on Runoff Processes: Urban and Suburban Development

Abstract: Urban and suburban development alters watershed imperviousness and connectivity, resulting in alterations to the hydrologic and hydraulic runoff response. Stormwater conveyance devices have been incorporated into most development to address the goal of floodwater removal for protection of life and property. Urban and suburban development laws generally consider the stormwater drainage system as part of the basic infrastructure and leave right of way and space to locate the component parts. Drainage systems are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…This finding is consistent with numerous studies that have found direct correlations between various land cover types and streamflow (e.g. Endreny, ; Schilling et al, ; Tu, ; Price et al, ). Land cover is also one of three primary factors – including soil type and slopes – that governs daily soil water retention in the SWAT model, a parameter in the curve number equation used to estimate daily surface runoff from different combinations of land cover, soil types, and slopes.…”
Section: Resultsmentioning
confidence: 98%
“…This finding is consistent with numerous studies that have found direct correlations between various land cover types and streamflow (e.g. Endreny, ; Schilling et al, ; Tu, ; Price et al, ). Land cover is also one of three primary factors – including soil type and slopes – that governs daily soil water retention in the SWAT model, a parameter in the curve number equation used to estimate daily surface runoff from different combinations of land cover, soil types, and slopes.…”
Section: Resultsmentioning
confidence: 98%
“…Urbanization is a major driver of land use change [Grimm et al, 2008] with water-related impacts styled as the "urban stream syndrome" (USS) [Walsh et al, 2005]. This stereotypes more rapid hydrologic response from impervious surfaces, increasing flood peaks, reducing time to peak, and restricting groundwater recharge, which diminishes base flows [Endreny, 2005]. The USS also encompasses pollution from road runoff and connected storm sewers and the resulting reduction in ecological status [Townsend-Small et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States (U.S.) urbanization, urban sprawl, and urban infilling are predominantly supplied by forest, agricultural, and grass lands (US GAO, 2001). These land cover changes disrupt the hydrological cycle and create increased runoff volumes (i.e., less surface storage and infiltration), increased velocities (i.e., less flow resistance and steeper, shorter flow paths), and elevated concentration of metals, sediment, and nutrients (Horner et al, 1994;Schueler, 1994;WEF ⁄ ASCE, 1998;Endreny, 2005). These land cover changes disrupt the hydrological cycle and create increased runoff volumes (i.e., less surface storage and infiltration), increased velocities (i.e., less flow resistance and steeper, shorter flow paths), and elevated concentration of metals, sediment, and nutrients (Horner et al, 1994;Schueler, 1994;WEF ⁄ ASCE, 1998;Endreny, 2005).…”
Section: Introductionmentioning
confidence: 99%